2023
DOI: 10.1002/aenm.202301921
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Room‐Temperature Synthesis of Large‐Scale, Low‐Cost, and Highly Active Ni─Fe Based Electrodes toward Industrialized Seawater Oxidation

Yuling Zhuo,
Dong Liu,
Lulu Qiao
et al.

Abstract: It is of significance to develop an active, efficient electrocatalyst for the oxygen evolution reaction (OER) as this determines the efficiency and cost of water/seawater electrolysis. Here, a cost‐effective Ni─Fe hydroxide as a promising OER catalyst is developed by 1 min ultrafast method. The catalyst shows low OER overpotentials of 240 and 254 mV at 10 mA cm−2 in both 1 m KOH and alkaline seawater, respectively. It also exhibits excellent electrochemical stability. In situ Raman spectra and other physical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…The presence of Ni 3+ species is important to form NiOOH as the active site for UOR (6NiOOH (s) + CO­(NH 2 ) 2(aq) + H 2 O (l) → 6Ni­(OH) 2(s) + N 2(g) + CO 2(g) ). , The Mo 2p and P 2p spectra of the used MoNiP/NF-0.50 electrode were almost the same as those in the fresh MoNiP/NF-0.50 electrode, respectively (Figure S8). Additionally, the peak observed at 550 cm –1 in the Raman spectra of the used MoNiP/NF-0.50 catalyst was assigned to the vibration of NiOOH, which was consistent with the results of XPS above (Figure S9A). SEM and TEM images showed that the honeycomb-like structural morphology and the elements’ distribution in the used MoNiP/NF-0.50 electrode all were the same as those in the fresh one (Figure S9B–G).…”
Section: Resultssupporting
confidence: 88%
“…The presence of Ni 3+ species is important to form NiOOH as the active site for UOR (6NiOOH (s) + CO­(NH 2 ) 2(aq) + H 2 O (l) → 6Ni­(OH) 2(s) + N 2(g) + CO 2(g) ). , The Mo 2p and P 2p spectra of the used MoNiP/NF-0.50 electrode were almost the same as those in the fresh MoNiP/NF-0.50 electrode, respectively (Figure S8). Additionally, the peak observed at 550 cm –1 in the Raman spectra of the used MoNiP/NF-0.50 catalyst was assigned to the vibration of NiOOH, which was consistent with the results of XPS above (Figure S9A). SEM and TEM images showed that the honeycomb-like structural morphology and the elements’ distribution in the used MoNiP/NF-0.50 electrode all were the same as those in the fresh one (Figure S9B–G).…”
Section: Resultssupporting
confidence: 88%
“…Fabrication of transition bimetallic hydroxides through a facile synthesis route at ambient temperature could enhance the performance of the OER. Zhuo et al 45 demonstrated a rapid, facile, cost-effective, and scalable (area: 2000 cm 2 ) synthesis route at room temperature for Ni(Fe)(OH) 2 , where it was synthesized by submerging the pre-cleaned Ni foam for 60 s in 0.2 M Fe(NO 3 ) 3 at ambient temperature, while it exhibits high activity and stability for the OER. The incorporation of Fe in Ni hydroxide and the in situ formation of Ni(Fe)OOH from Ni(Fe)(OH) 2 during electrolysis are attributed to the enhancement in the performance for the OER.…”
Section: Constructing Noble Metal-free Electrocatalysts For the Her A...mentioning
confidence: 99%
“…In the era of increasing energy crisis and environmental pollution, finding efficient, clean, and environmentally sustainable energy has become an urgent issue. Hydrogen energy is acknowledged as an eco-friendly, sustainable, and substitute energy solution to meet the worldwide demand for 60% of global energy. Currently, various methods for hydrogen production have been developed by the scientific community, including thermochemical processes, biological approaches, direct solar water decomposition, and electrolytic water splitting. Among them, hydrogen generation through electrochemical water splitting is the most promising approach, as it is a sustainable pathway with low complexity. To date, Pt-based materials have shown exceptional activity in the hydrogen evolution reaction (HER), but their scarcity and cost make them unsuitable for practical use. Consequently, it is essential to develop water splitting by utilizing efficient, inexpensive, and abundant reserve-based non-noble-metal electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%